DETERMINANTS OF CASH WAQF CONTRIBUTION IN KLANG VALLEY AND SELANGOR: A SEM APPROACH - Sakti, Muhammad Rizky Prima; bin Mohd Thas Thaker, Hassanuddin; Qoyum, Abdul; Qizam, Ibnu (Bank Indonesia, 2016)
Cash waqf is becoming one of the popular Islamic financial instruments which not only focus on the religiosity but also has significant impact to the ummah development. This waqf scheme does not require richness in wealth, yet everybody in the society can contribute to cash waqf. The importance of cash waqf is getting popular as it has benefited in many ways, for example it can be used to develop assets and abandoned land for business and agricultural purposes. In addition, cash waqf also can be utilized to help institutions who are facing financial problem or liquidity issues. Nonetheless, rarely we found in the literature that empirically examines the cash waqf determinants and contributions. This paper is one of the few empirical studies that investigate the determinants towards the contribution of cash waqf in Malaysia. The purpose of this paper is to investigate the main factors that influence people towards the contribution of cash waqf instruments, special reference to the Klang Valley and Selangor. This paper employs structural equation modeling (SEM) to verify the determinants of cash waqf contribution. In doing so, we use primary data by distributing self-administrated questionnaire constituting a sample of 114 respondents from Klang Valley and Selangor. Our empirical results reveal that the main factors that driven people towards the contribution of cash waqf products are attitude and social influences, however interestingly religion obligation is not influence the contribution of cash waqf.